Association between left atrial appendage volume and atrial fibrillation recurrence after catheter ablation: a systematic review and meta-analysis - Chen Chen; Pengfei Chen; Dazhuo Shi; Deng Pan; Ming Guo; Jianpeng Du (BMJ Open)
Objectives To evaluate the association between left atrial appendage volume (LAAV) and atrial fibrillation (AF) recurrence after catheter ablation (CA) and explore the potential mechanism.Design Systematic review and meta-analysis.Data sources PubMed, EMBASE, Web of Science and Cochrane Library databases were searched systematically from inception through 28 September 2024 to identify relevant studies.Eligibility criteria Observational studies that estimated the association between LAAV and AF recurrence.Data extraction and synthesis Two independent investigators screened studies for inclusion and extracted data. Statistical heterogeneity was assessed using the Cochrane Q-test and I², with p<0.1 or I² > 50% indicating significant heterogeneity. This study used a random-effects model to account for potential heterogeneity. The quality of the included studies was assessed using the Newcastle–Ottawa Scale (NOS), Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I tool) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Publication bias was examined through funnel plots and Egger’s test.Result Seventeen studies (3078 patients) were included. Meta-analysis of 11 studies suggested that LAAV was significantly associated with the risk of AF recurrence in both univariate (HR 1.06, 95%CI 1.04 to 1.08, p<0.01; I2=49.7%) and multivariate analyses (HR 1.10, 95%CI 1.05 to 1.16, p<0.01; I2=77.4%). The relationship between LAAV and recurrence of persistent AF (HR 1.11, 95% CI 1.03 to 1.20, p<0.05; I² = 73.0%) was significant. However, no significant association was found for paroxysmal AF (HR 1.01, 95% CI 0.94 to 1.07, p>0.05; I² = 0%). Meta-analysis of 13 studies suggested that patients with recurrence had larger LAAV values than those without recurrence (standardised mean difference (SMD) 0.54, 95% CI 0.36 to 0.71, p<0.01; I2=67.9%), and persistent AF patients had larger LAAV values than paroxysmal AF (SMD 0.29, 95% CI 0.02 to 0.57, p=0.05; I2=60.6%). Sensitivity analyses did not change these results. Subgroup analyses largely aligned with the overall findings, though study design and sample size contributed to heterogeneity. The mean NOS scores indicated moderate to high study quality; ROBINS-I assessments showed that most studies had a low to moderate overall risk of bias; and the GRADE approach rated the certainty of outcome evidence as low.Conclusions Our study suggests that LAAV may be a significant predictor of AF recurrence after CA. Incorporating LAAV into pre-ablation screening may enhance risk stratification, guiding tailored follow-up and treatment strategies.PROSPERO registration number CRD42022339910.